“The iron fist, the leather glove, and the woollen mitten” : gender performance(s), complicity, and complacency in written and screen versions of Aunt Lydia from Margaret Atwood’s The Handmaid’s Tale and The Testaments - Nöffke, Tobias Georg (University of Pretoria, 2023)
Dissertation (MA (English))--University of Pretoria, 2022.